Accuracy of Triage Systems in Disasters and Mass Casualty Incidents; a Systematic Review - Bazyar, Jafar; Farrokhi, Mehrdad; Salari, Amir; Safarpour, Hamid; Khankeh, Hamid Reza (Archives of Academic Emergency Medicine, 2022)
Introduction: To prioritize patients to provide them with proper services and also manage the scarce resources in emergencies, the use of triage systems seems to be essential. The aim of this study was to evaluate the accuracy of the existing triage systems in disasters and mass casualty incidents. Methods: The present study is a systematic review of the accuracy of all triage systems worldwide. The results of this study were based on the articles published in English language journals. In this research, all papers published from the beginning of 2000 to the end of 2021 were sought through different databases. Finally, a total of 13 articles was ultimately selected from 89 articles. Results: 13 studies on the accuracy of triage systems were reviewed. The START, mSTART, SALT, Smart, Care Flight, ASAV, MPTT, Sieve and ESI triage systems, had an accuracy, sensitivity, and specificity of less than 90%. Only the Smart triage system had an overall accuracy of more than 90%. Conclusion: According to the findings of the current systematic review, the performance of the existing triage systems in terms of accuracy of prioritizing the injured people and other performance indexes is not desirable. Therefore, to improve the performance and increase the precision of triage systems, the world nations are recommended to change or revise the indexes used in triage models and also identify other influential factors affecting the accuracy of triage systems.